Implementing Deep Learning as a Pedagogical Approach in Elementary Fine Arts Education: A Qualitative Case Study of Student Creativity - Muh. Ahyar; Andi Imrah Dewi; Kadek Hariana; Nurul Fitriah Aras; Kasmawati (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2026)
This study explores the implementation of Deep Learning as a pedagogical approach to supporting student creativity in fourth-grade Fine Arts education at SD Inpres Perumnas Palu. A qualitative single-case study was conducted involving one Fine Arts teacher and 25 fourth-grade students. Data were collected through classroom observations, semi-structured interviews with the teacher and selected students, and documentation, and were analysed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The findings showed that the Deep Learning approach was enacted through five interconnected stages: learning planning, stimulus and orientation, idea exploration, the creative process, and reflection. The use of recycled plastic bottles as functional flower pots connected artistic expression with environmental awareness, practical design, and students’ everyday experiences. Students displayed creative behaviours through fluency, flexibility, originality, and elaboration, as reflected in alternative sketches, modified designs, varied decorative choices, functional features, and revisions after feedback. However, student participation was uneven; while some students worked independently, others required examples, encouragement, repeated prompts, or practical assistance. Teacher facilitation through reflective questioning, feedback, motivation, and differentiated scaffolding was therefore important in supporting meaningful participation. The study illustrates how Deep Learning can support contextual and creativity-oriented Fine Arts learning using accessible recycled materials. Keywords: Student Creativity, Deep Learning, Fine Arts, Elementary School